Factors Affecting the Incidence of Disease Due to Employment Relationship at PT. Indrabakti Mustika North Konawe - Zainal, Zainal; Azizi Jayadipraja, Erwin; Aziz Harun, Abdul (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: The results of interviews with 10 workers illustrate that aspects of workers' health are disturbed, namely many workers who have suffered injuries, decreased attendance due to illness, exposure to mineral dust from the location or conditions of mining areas with dry and sandy soil structures that can cause silicosis or exposure to noise sourced from the operation of work tools. The purpose of the study is to determine the factors related to diseases due to labor relations in nickel mine workers at PT. IndrabaktiMustikaKonawe North. Methods: This study uses a Cross sectional Study approach. The study has been carried out for 30 days. The population numbered 568 people. The Research Sample totaled 82 samples. The sample technique in this study is Simple Random Sampling. The data were processed using the Data Normality Test (Kolmogrov Smirnov Test) Chi Square Test. Result: The results showed that there was a relationship between age X2hits = 14,024 > X2 tabs = 3,841, length of work X2hits = 7,678 >X2 tabs = 3,841 and air temperature X2hits = 15,752 >X2 tabs = 3,841 to diseases due to labor relations in nickel mine workers at PT. IndrabaktiMustika North Konawe. Conclusion: Research shows that there is a relationship between age, noise and PPE use to diseases due to labor relations in nickel mine workers in PT. IndrabaktiMustika North Konawe.